2022
DOI: 10.3390/nano12193484
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver, Gold, and Platinum Doped Zinc Oxide Nanoparticles by Pulsed Laser Ablation in Water

Abstract: In this paper, we propose a simple two-step method for the synthesis of Ag, Au, and Pt-doped ZnO nanoparticles. The method is based on the fabrication of targets using the pulsed laser deposition (PLD) technique where thin layers of metals (Ag, Pt, Au) have been deposited on a metal-oxide bulk substrate (ZnO). Such formed structures were used as a target for the production of doped nanoparticles (ZnO: Ag, ZnO: Au, and ZnO: Pt) by laser ablation in water. The influence of Ag, Au, and Pt doping on the optical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…The Ag, Ag/Au, Au, and Au/Ag thin layer electrodes on ITO glass substrates had values of 1.636, 1.445, 1.573, and 1.598 eV, respectively. The value of the band gap energy for each type of electrode has a value that is not much different because the band gap energy of pure Ag and Au also has almost the same value [33]. This indicates that all the formed thin films can be classified as narrow band gap semiconductors.…”
Section: Resultsmentioning
confidence: 87%
“…The Ag, Ag/Au, Au, and Au/Ag thin layer electrodes on ITO glass substrates had values of 1.636, 1.445, 1.573, and 1.598 eV, respectively. The value of the band gap energy for each type of electrode has a value that is not much different because the band gap energy of pure Ag and Au also has almost the same value [33]. This indicates that all the formed thin films can be classified as narrow band gap semiconductors.…”
Section: Resultsmentioning
confidence: 87%
“…The decrease in dislocation density in case of W doped CuO nanoparticles represents a decrease in the content of lattice imperfections and indicates the formation of better quality of nanoparticles. The microstrain decreased in case of single and bi-metal doping CuO nanoparticles due to reduction in lattice distortion in the crystal structure of CuO nanoparticles as shown in table 2 [45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 98%
“…The division at around 6 eV between the Ag(3d 3/2 ) 373.29 eV and Ag(3d 5/2 ) 367.28 eV peaks showed that the silver in the synthesized samples was metallic [33]. Because Ag 2 O has the same binding energies as Ag-O, these peaks are likewise connected to Ag−O bonding [53].…”
Section: Morphological Analysismentioning
confidence: 94%